ANALISIS KESALAHAN BERBAHASA PADA BUKU SISWA KURIKULUM 2013 TEMA “LINGKUNGAN SAHABAT KITA” KELAS V SEKOLAH DASAR - Rizka Nur Oktaviani; Melindha Dia Ayu Wulandari (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2021)
The problem that would be examined in this research was analyzing language errors in the use of letters and punctuation in the 2013 curriculum student book with the theme "Environment of Our Friends" for grade 5 Elementary School published by the Ministry of Education and Culture of the Republic of Indonesia. This study aimed to describe (1) the level of errors in the use of letters and (2) the level of errors in the use of punctuation, in the 2013 curriculum student book with the theme "Environment is Our Friend" for fifth grade Elementary School published by the Ministry of Education and Culture of the Republic of Indonesia. This study used a qualitative descriptive approach. The data collection techniques used were in the form of a census (complete enumeration), in-depth observation (systematic observation) and using information sources in the form of books or documentation of previous research. The results of the research obtained, namely language errors in the 2013 curriculum students' books with the theme “Environment is Our Friend” for class V Elementary School were errors in the use of letters and the use of punctuation. Errors in the use of letters amounted to 136 (41.21%) and punctuation marks totaled 194 (58.79%). The level of language errors in the use of letters and punctuation was with the conversion value ranges from 41% -60% with sufficient criteria. Keywords: language errors, 2013 curriculum student book. References:   Ariningsih, N.E., Sumarwati, &  Saddhono, K. 2012. Analisis Kesalahan  Berbahasa Indonesia  Dalam Karangan Eksposisi Siswa  Sekolah Menengah Atas.BASASTRA. 1 (1). 40-53. Farhani, I.R. 2015. Analisis Kesalahan EYD (Ejaan Yang Disempurnakan) pada Buku Teks Bahasa Indonesia Ekspresi Diri dan Akademik Kelas X Kurikulum 2013. Jakarta: Universitas Islam Negeri Syarif Hidayatullah. Markhamah & Sabardila, A. 2014. Analisis Kesalahan dan Karakteristik Bentuk Pasif. Surakarta: Muhammadiyah University Press. Nurwicaksono, B.D. & Amelia, D. 2018. Analisis Kesalahan Berbahasa Indonesia Pada Teks Ilmiah Mahasiswa. Jurnal Aksis 2 (2). 138-153.  Prastowo, A. 2019. Analisis Pembelajaran Tematik Terpadu. Jakarta: Kencana. Qhadafi, M.R. 2018. Analisis Kesalahan Penulisan Ejaan yang Disempurnakan dalam Teks Negosiasi Siswa SMA Negeri 3 Palu. Jurnal Bahasa dan Sastra, 3(4), 3. Rosita, Y.R, & Achsani, F. 2018. Ketidakefektifan Kalimat Dalam Karangan Liburan Siswa Kelas X SMK X IPTEK Weru. Wahani 2 (2). 21-32. Suandi, I.N., Sudiana, I.N., & Nurjaya., I.G. 2018. Keterampilan Berbahasa Indonesia Berorientasi Integrasi Nasional dan Harmoni Sosial. Depok: PT RajaGrafindo Persada. Sudijono, A. 2014. Pengantar Statistik Pendidikan. Jakarta: PT Raja Grafindo Persada. Sugiyono. 2018. Metode Penelitian Kuantitatif, Kualitatif, dan R&D. Bandung: Alfabeta. Supriani, R. & Siregar, I.R. 2012. Penelitian Analisis Kesalahan Berbahasa.Jurnal Edukasi Kultura. 4(2). 67-76. Setyawati, N. 2017. Analisis Kesalahan Berbahasa Indonesia Teori dan Praktik. Kadipiro Surakarta: Yuma Pustaka.